C-reactive protein lowers the serum level of IL-17, but not TNF-α, and decreases the incidence of collagen-induced arthritis in mice - Singh, Sanjay K.; Prislovsky, Amanda; Ngwa, Donald N.; Munkhsaikhan, Undral; Abidi, Ammaar H.; Brand, David D.; Agrawal, Alok (Frontiers in Immunology, 2024)
The biosynthesis of C-reactive protein (CRP) in the liver is increased in inflammatory diseases including rheumatoid arthritis. Previously published data suggest a protective function of CRP in arthritis; however, the mechanism of action of CRP remains undefined. The aim of this study was to evaluate the effects of human CRP on the development of collagen-induced arthritis (CIA) in mice which is an animal model of autoimmune inflammatory arthritis. Two CRP species were employed: wild-type CRP which binds to aggregated IgG at acidic pH and a CRP mutant which binds to aggregated IgG at physiological pH. Ten CRP injections were given on alternate days during the development of CIA. Both wild-type and mutant CRP reduced the incidence of CIA, that is, reduced the number of mice developing CIA; however, CRP did not affect the severity of the disease in arthritic mice. The serum levels of IL-17, IL-6, TNF-α, IL-10, IL-2 and IL-1β were measured: both wild-type and mutant CRP decreased the level of IL-17 and IL-6 but not of TNF-α, IL-10, IL-2 and IL-1β. These data suggest that CRP recognizes and binds to immune complexes, although it was not clear whether CRP functioned in its native pentameric or in its structurally altered pentameric form in the CIA model. Consequently, ligand-complexed CRP, through an as-yet undefined mechanism, directly or indirectly, inhibits the production of IL-17 and eventually protects against the initiation of the development of arthritis. The data also suggest that IL-17, not TNF-α, is critical for the development of autoimmune inflammatory arthritis.